2004
DOI: 10.1038/sj.onc.1207489
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogen-induced colon tumors in mice are chromosomally stable and are characterized by low-level microsatellite instability

Abstract: The azoxymethane (AOM)-induced mouse colon tumor model recapitulates many of the histopathological features associated with the multistage progression of human sporadic colorectal cancers (CRCs). To better define the genetic events associated with tumorigenesis in this murine model, we analysed tumors from A/J mice for chromosomal (CIN) and microsatellite (MSI) instabilities, two fundamental pathways of genomic instability that play a critical role in the pathogenesis of human CRCs. Male A/ J mice, 6-week old,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 42 publications
(61 reference statements)
7
29
2
1
Order By: Relevance
“…Although these numerical differences suggested that gefitinib might inhibit the development of tumors with K-ras mutations, they did not reach statistical significance (P = 0.09). Moreover, this frequency of K-ras mutations was in agreement with prior reports (41). Because Ras was WT (and therefore regulated by EGFR) in ACF from gefitinibtreated animals, we infer that gefitinib would inhibit EGFR downstream effectors, such as ERK, an effector of Ras, in these ACF.…”
Section: Below)supporting
confidence: 92%
“…Although these numerical differences suggested that gefitinib might inhibit the development of tumors with K-ras mutations, they did not reach statistical significance (P = 0.09). Moreover, this frequency of K-ras mutations was in agreement with prior reports (41). Because Ras was WT (and therefore regulated by EGFR) in ACF from gefitinibtreated animals, we infer that gefitinib would inhibit EGFR downstream effectors, such as ERK, an effector of Ras, in these ACF.…”
Section: Below)supporting
confidence: 92%
“…Azoxymethane induces large numbers of ACF and adenocarcinomas that are confined to the distal colon. In addition, because there is a gradual loss of Apc, the role of PGE 2 in h-catenin signaling can be evaluated during ACF formation (21,(30)(31)(32). Our results showed that loss of mPGES-1 significantly reduced ACF size, suggesting that promotion associated with PGE 2 can also occur early during tumorigenesis.…”
Section: Cancer Researchmentioning
confidence: 68%
“…PGE 2 has been shown to play a role in the indirect activation of hcatenin via inactivation of Axin and glycogen synthase kinase 3h (GSK-3h), proteins that form part of the h-catenin degradation complex (29). Unlike the complete loss of Apc function that occurs in Apc D14/+ -derived adenomas, the loss of Apc protein is a gradual process following azoxymethane treatment, accompanied by increased cytoplasmic and nuclear staining of h-catenin (21,(30)(31)(32).…”
Section: D14/+mentioning
confidence: 99%
“…We previously reported that the forcible transfection of mPGES-1 in combination with COX-2 into HEK293 cells led to cellular transformation with a concomitant and robust increase in PGE 2 (Kamei et al, 2003). It was also shown that overexpression of COX-2 induced genomic instability in MCF10A breast cancer cells (Singh et al, 2007) and that AOM-induced colon tumors in mice were chromosomally stable and were characterized by low-level microsatellite instability (Guda et al, 2004). mPGES-1-derived PGE 2 might enhance chemical carcinogen-initiated colon carcinogenesis by the induction of genomic instability.…”
Section: Discussionmentioning
confidence: 99%